Effect of Genistein on Proliferating Cell Nuclear Antigen (PCNA) Expression and Vascular Density in The Peritoneum of Endometriosis Mice Model - Anggia Prameswari Wardhana; Yahya Irwanto (Asian Journal of Health Research, 2023)
Introduction: Survival of endometriosis lesions depends on the formation of blood vessels, cell proliferation, and oxygen supply. Their vascular densities can evaluate the vascularity of ectopic endometriosis tissues. Proliferating Cell Nuclear Antigen (PCNA) is one of the markers of cell proliferation that affects the growth of endometriotic lesions. Genistein is an isoflavone component that highly potential effect as an anti-angiogenic and inhibiting proliferation through the binding capacity to estrogen receptors. Material and Methods: This experimental study uses the Stored Biological Materials of mice peritoneum tissue. The paraffin block was divided into six groups, which are the negative control group, positive control group, and four treatment groups with genistein doses of 1.3 mg/day, 1.95 mg/day, 2.6 mg/day, and 3.25 mg/day. Immunohistochemical techniques and hematoxylin-eosin for vascular densities examined PCNA expressions. Preparation analysis uses OLIVIA software. Preparation calculations are done manually with cell count software. Observations were analyzed with the ANOVA test and Dunnett T3 5% test. Results: Based on analysis with ANOVA, there was a significant difference in PCNA expression and vascular densities because of the effect of genistein in various doses with a p-value of 0.001 (p<0.05). Based on Dunnett T3 5% test increase of PCNA expression by giving genistein doses 1,3 mg/day, 1,95 mg/day, and 2,6 mg/day, a reduction in dose of 3,25 mg/day. Vascular densities reduced significantly in all treatment groups. Conclusion: Administration of genistein in various doses significantly increases PCNA expression but reduces PCNA expression in a dose of 3.25 mg/day and significantly reduces vascular densities.